Top−k Retrieval in Description Logic Programs Under Vagueness for the Semantic Web - Lukasiewicz, T; Straccia, U (Springer, 2007)
Description logics (DLs) and logic programs (LPs) are important representation languages for the Semantic Web. In this paper, we address an emerging problem in such languages, namely, the problem of evaluating ranked top-k queries. Specifically, we show how to compute the top-k answers in a data-complexity tractable combination of DLs and LPs under vagueness.